Replantation services in a Malaysian Public Hospital - Mohd Kasim, Kamil; Khalid, Kamarul Ariffin; Mohd Yusof, Nazri; Mohammad Amin, Mohammad Azril (2007)
Replantation services are a highly specialized field and are usually rendered by a tertiary centre in most hospitals around the world. Usuallv these centres would have an existing established plastic surgery unit or dedicated hand depaftment. In a developing country like Malaysia, replantation services also do exist and are mainly taken care by few centres with established hand units. This service is offered by our hospital, which is a public hospital with no established plastic surgery or hand surgery unit. This service was started in early 2005 and we would like to share our experiences. Majority of the cases are from industrial injuries and most of these cases are from remote areas. We have about 11 cases of partial amputation injuries and 7 total amputations. For the revascularization cases, we obtained 100% success rate. and about 80% of replantation cases. We would like to share our experience of success and failures in building up a highly specialized field of orthopaedic sub-specialization.